2020
DOI: 10.1111/ina.12642
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection by in‐duct ultraviolet lamps under different environmental conditions in turbulent airflows

Abstract: In this study, we investigated the effects of environmental factors such as airflow velocity, relative humidity (RH), temperature, and duct reflectance on the performance of in‐duct UVC lamps. Staphylococcus epidermidis, Pseudomonas alcaligenes, and Escherichia coli were used as the test bacteria. The UV irradiance, disinfection efficacy, and UV susceptibility constant (Z value) of the test bacteria were experimentally determined. The results showed that the UV disinfection efficacy decreased as the airflow ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 35 publications
3
43
0
Order By: Relevance
“…Zhang et al [ 132 ] have studied the factors that affect the performance of UVC lamps installed in the duct as a means of killing bacteria and viruses. They included airflow velocity, relative humidity (RH), temperature, and duct reflectance.…”
Section: Indoor Air Quality (Iaq)mentioning
confidence: 99%
“…Zhang et al [ 132 ] have studied the factors that affect the performance of UVC lamps installed in the duct as a means of killing bacteria and viruses. They included airflow velocity, relative humidity (RH), temperature, and duct reflectance.…”
Section: Indoor Air Quality (Iaq)mentioning
confidence: 99%
“…Regarding the flow rate, environmental factors such as temperature, humidity, and pipe reflectivity have an impact on the UVC lamp with sensor. Performance impact studies have also shown that with an increase in air velocity and relative humidity, the bactericidal effect decreases to a certain extent [103]. Comparison of UVC to performance ratio at low (15-16 • C) and higher temperatures (25-26 • C) reveal that UVC has a maximum sterilization effect at a temperature of 20-21 • C.…”
Section: Deep Ultraviolet Led Disinfection Applicationmentioning
confidence: 99%
“…Harvard School of Public Health's past research on UVGI technology by First et al 9,16,17 has provided guidelines that mainly focus on the microorganism inactivation potential of this technology. Other studies have examined the disinfection efficacy of in‐duct UVGI system 18,19 . Here we focus on the impact of room design on the effectiveness of upper‐room UVGI and the safety of the lower zone of the room.…”
Section: Introductionmentioning
confidence: 99%